Random reward priming is task-contingent: the robustness of the 1-trial reward priming effect - Ásgeirsson, Árni G.; Kristjánsson, Árni (Frontiers in Psychology, 2014)
Consistent financial reward of particular features influences the allocation of visual attention in many ways. More surprising are 1-trial reward priming effects on attention where reward schedules are random and reward on one trial influences attentional allocation on the next. Those findings are thought to reflect that rewarded features become more salient than unrewarded ones on the subsequent trial. Here we attempt to conceptually replicate this effect, testing its generalizability. In three versions of an analogous paradigm to the additional singleton paradigm involving singleton search for a Gabor patch of odd spatial frequency we found no evidence of reward priming, while we only partially replicate the reward priming in the exact original paradigm tested by Hickey and colleagues. The results cast doubt on the proposal that random reward enhances salience, suggested in the original papers, and highlight the need for a more nuanced account. In many other paradigms reward effects have been found to progress gradually, becoming stronger as they build up, and we argue that for robust reward priming, reward schedules need to be more consistent than in the original 1-trial reward priming paradigm.